NILAI MORAL DALAM KUMPULAN CERITA RAKYAT GADIS KELADI DAN PANGERAN ULAT TANDUK KARYA MARIYADI - Agnes Natalia Midah Semi; Sesilia Seli; Agus Wartiningsih (Universitas Tanjungpura, 2020)
Abstract The background of this research is to describe the moral values in the folklore of the Keladi Girl and Pangeran Ulat Tanduk by Mariyadi. This study reveals four subproblems, namely moral values in a collection of GKPUT folklore that illustrates the relationship between humans and God. about, and the planned implementation of the results of this research in learning Indonesian in high school. The main theories used in this study are folklore, moral values, and Indonesian language learning theory. The method in this research is descriptive qualitative. The approach used in this research is sociology of literature. The date source in this study is Mariyadi's GKPUT folklore. Data collection techniques in this research are documentary studies. The results of this study are: 1) moral values in a collection of GKPUT folklore that illustrate the relationship between humans and God, which are giving thanks, praying, and respecting parents; 2) moral values in a collection of GKPUT folklore stories that describe human relationships with fellow human beings, namely love, care, awareness, and sadness; 3) moral values in a collection of GKPUT folklore that illustrate the relationship between humans and the environment, namely loving animals. As well as the implementation of student learning in X even semester 2013 curriculum. KD identifies the values and content contained in Folklore both oral and written. The results of this study are expected to be useful for all levels, especially teachers, and general readers. Keywords. Moral Value, Folklore, GKPUT.